ANALISIS DAMPAK KANDUNGAN GAS TETRAFLOROETANA TERHADAP KEKUATAN DIELEKTRIK GAS KARBONDIOKSIDA DALAM MEDAN TINGGI DC BATANG-BATANG - Bagas Azzanazaki Nurbyantoko; Moch. Dhofir; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2022)
This study describes the effect of tetrafluoroethane gas concentration on the dielectric of carbon dioxide gas in a high field dc rods. This research begins with data collection through breakdown voltage testing at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Universitas Brawijaya. Variations of conditions used in the breakdown voltage test include changes in the concentration of R134 gas in CO2 gas of 0%, 10%, 20%, and 30% which are calculated based on the total pressure of the mixed gas, the variation of the total pressure of the mixed gas is 2000 mBar, 2200 mBar, 2400 mBar, and 2600 mBar, as well as changes in the gap between 2 cm and 1 cm. The test is carried out using high DC voltage. The arrangement of the electrodes used is rods. The results obtained in this study are the influence of the concentration of R134 gas in CO2 gas where the value of the dielectric strength of pure R134 gas is higher than that of contaminated CO2 gas. In addition, variations in the ratio of R134 gas concentration from 0% to 30% and variations in the ratio of total mixed gas pressure from 2000 mBar to 26000 mBar affect the dielectric strength of the mixed gas. Where the greater the value of CO2 gas concentration, the smaller the breakdown voltage value. while the greater the value of the total pressure of the mixed gas, the greater the value of the breakdown voltage. Keywords— Gas Insulator, Tetrafluoroethane, carbondioxide, Breakthrough Voltage, Dielectric Strength.